Three branches of literary anthropology: Sources, styles, subject matter - Wiles, Ellen (Ethnography, 2020)
‘What is literary anthropology?’ – a deceptively simple question, posed by anthropologist Paul Stoller – unleashes debate about the perceived identity of the field. Through the lens of three book reviews, this essay proposes conceptualizing literary anthropology as a central stem with three branches. The first is the use of literary texts as ethnographic source material, particularly for historical anthropologists. The second is the use of literary modes of writing ethnography, ranging from the incorporation of metaphorical language and the subversion of conventional ethnographic structures to the production of fiction as ethnography. The third is the anthropological examination of literary cultural and production practices. The third has been underexplored in the academy to date, the second has been at the centre of fierce controversy within the wider field of anthropology, while the first has arguably been limited by restrictive disciplinary and epistemological assumptions.